Distinct magnetic fabric in weakly deformed sediments from extensional basins and fold‐and‐thrust structures in the Northern Apennine orogenic belt (Italy). Issue 2 (6th February 2016) - Caricchi, Chiara; Cifelli, Francesca; Kissel, Catherine; Sagnotti, Leonardo; Mattei, Massimo
Abstract: We report on results from anisotropy of magnetic susceptibility (AMS) analyses carried out on weakly deformed fine‐grained sediments from the Northern Apennine orogenic system (Italy). We sampled 63 sites from preorogenic, synorogenic, and postorogenic sequences, which differ in age, composition, depositional environment, degrees of deformation, and tectonic regimes. The magnetic fabric is typical of weakly deformed sediments, with a magnetic foliation subparallel to the bedding plane and a magnetic lineation well defined in this plane. Northern Apennine chain deposits are characterized by strongly oblate magnetic susceptibility ellipsoids, indicating that the magnetic fabric is the result of both compaction process and tectonic load experienced by the sediments during diagenesis and orogenic events. The orientation of magnetic lineation is significantly different depending whether the studied sites underwent extensional or compressional tectonic regimes. In the Northern Apennine chain, the magnetic lineation is mostly oriented NNW‐SSE, parallel to the main compressional structures. It suggests a tectonic origin of the magnetic lineation with an acquisition related to the Apennines compressional phases. In the extensional Tuscan Tyrrhenian margin, magnetic lineation is oriented ENE‐WSW, almost perpendicular to the main extensional faults, which represent the main deformation elements of the area. Our results demonstrate a close relationship between the shape and orientation of magnetic fabric and the tectonic history of rocks, confirming that AMS represents a valuable tool to investigate the tectonic history of weakly deformed sedimentary rocks. Key Points: We compare magnetic fabric from diversified deposits in the same orogenic system Measured AMS from Northern Apennines is typical of weakly deformed sediments A close relationship between magnetic fabric and tectonics is observed